МИТНА БЕЗПЕКА ЯК ВАЖЛИВА СКЛАДОВА ЕКОНОМІЧНОЇ БЕЗПЕКИ ДЕРЖАВИ - Новосад, Ірина Василівна (Науковий журнал «Світ фінансів», 2017)
Новосад І. В. Митна безпека як важлива складова економічної безпеки держави. Визначено місце та роль митної безпеки як складової економічної безпеки держави. Встановлено й обґрунтовано взаємозв’язок між економічною безпекою та митною безпекою. Розкрито сутність економічної безпеки та визначено роль митної безпеки у її забезпеченні. Розглянуто вплив митної безпеки на стан національної економіки. Окреслено інтереси держави у сфері митної безпеки та наведено етапи її реалізації, розглянуто джерела загроз митній безпеці держави. Визначено пріоритетні завдання митних органів захисту національних інтересів та забезпечення митної безпеки держави з урахуванням досвіду провідних країн світу. Новосад И. В. Таможенная безопасность как важная составляющая экономической безопасности государства. Определению место и роль таможенной безопасности как составляющей экономической безопасности государства. Установлено и обоснованно взаимосвязь между экономической безопасностью и таможенной безопасностью. Раскрыта сущность экономической безопасности и определена роль таможенной безопасности в ее обеспечении. Рассмотрено влияние таможенной безопасности на состояние национальной экономики. Очерчены интересы государства в сфере обеспечения таможенной безопасности и приведены этапы ее реализации, рассмотрены источники угроз таможенной безопасности государства для дальнейшего их предотвращения. Определены приоритетные задачи таможенных органов в контексте защиты интересов и обеспечения таможенной безопасности государства с учетом опыта ведущих стран мира. Novosad I. Customs security as an important component of economic security. The article is devoted to defining the place and role of customs security as a component of economic security. Established and grounded relationship between economic security and customs security. The essence of economic security and the role of customs security to economic security. The influence of customs security on the state of the national economy. Studied the customs interests of the state; are the stages of customs security sources considered security threats Customs for further prevention. The priority task of customs authorities to protect national interests and ensuring the security of the State Customs from the experience of leading countries. Introduction. The development of market relations, intensification of export-import operations, strengthening international economic cooperation and integration processes around the world accompanied by aggravation of economic competition. At this time activates the negative impact of external factors on customs security Ukraine: increase the number of subjects who commit violations of customs regulations, smuggling growth, reduction of customs duties. Purpose. Generalization of theoretical approaches to the definition of “Customs Security”, its analysis and structure determination of the role of customs security as an important component of economic security. Results. Increased integration in the world economy, Ukraine’s accession to the WTO, the national economy is increasingly dependent on foreign economic activity of the country. Therefore, foreign trade, customs security as a component of economic security is becoming more important for Ukraine. Customs security – a state protected the economic interests of the state, which provides a variety of external and internal conditions, regardless of any threats: – Movement across the customs border of Ukraine and vehicles; – Сustoms regulation relating to the installation dimensions customs duties and completeness of their collection; – The application of customs procedures, measures of customs and tariff and non-tariff regulation; – Combating smuggling and customs violations; – Perform other assigned tasks to the customs authorities. Customs security actively influence the content of the budget and protect national interests. However, during its implementation meets many problems: – The need to reduce the impact of human factors on the process of customs clearance, which should reduce the share of “gray” and “black” imports; – The constant lowering of customs value of imported goods to reduce customs duties; – The need for constant improvement of interaction with the authorities of neighboring states; – Reduction of social protection of the customs authorities. Conclusion. The priority task of customs authorities is to protect the national interest, but it is advisable to take into account the experience of leading countries, namely: – Emphasize the priority of national interests in the regulation of foreign trade; – Approve the principles of reciprocity in granting trade preferences partners and compliance requirements of fair competition; – To provide for the protection of national economic security by administrative regulation export; – To provide a detailed legal regulation of working all instruments of foreign economic activities and improve the living standards of workers social customs. The positioning of clear priorities will enable the customs authorities at minimal cost to ensure effective cooperation with law enforcement bodies of the country and maximize revenues for the state budget.